2014
DOI: 10.1111/jfq.12080
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum Flour Characterization and Evaluation in Gluten‐Free Flour Tortilla

Abstract: Four sorghum hybrids ), Fontanelle-1000 [F-1,000], ATx631xRTx2907 [NE#20] and 5,040C) were characterized and evaluated for kernel characteristics, proximate analysis, flour characterization (particle size distributions, starch damage, amylose content and starch pasting properties) and end product in gluten-free tortilla. A commercial sorghum flour (TVM) was used as a control. Significant differences were found (P < 0.05) among hybrids for kernel and flour composition except total starch (P > 0.05). NE#20 had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
5
29
3
2
Order By: Relevance
“…Table shows the chemical composition of sorghum flour, where it can be observed that there were found significant differences among the hybrids of sorghum flour, with ash content varying from 0.27 to 1.03% (db) for DK51 and PbCr, respectively. In contrast, Liu et al and Winger et al reported higher values for ash content (around 1.4% db) in decorticated sorghum flour. Several authors have found that sorghum flour with a low ash content has better baking properties , and in the present study no samples exceeded the 1.5% ash limit established by the Codex Alimentarius .…”
Section: Resultsmentioning
confidence: 85%
“…Table shows the chemical composition of sorghum flour, where it can be observed that there were found significant differences among the hybrids of sorghum flour, with ash content varying from 0.27 to 1.03% (db) for DK51 and PbCr, respectively. In contrast, Liu et al and Winger et al reported higher values for ash content (around 1.4% db) in decorticated sorghum flour. Several authors have found that sorghum flour with a low ash content has better baking properties , and in the present study no samples exceeded the 1.5% ash limit established by the Codex Alimentarius .…”
Section: Resultsmentioning
confidence: 85%
“…However, consumption of grain sorghum has been increasing with the growing demand for gluten‐free foods. Sorghum has been successfully utilized in a variety of food products catering to this industry (Huang and others ; Rooney and Waniska ; Schober and others , ; Liu and others ; Winger and others ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the US gluten-free food and beverage sales are expected to surpass $6.6 billion by 2017 [2]. Nevertheless, most of the time nutritional status and demands of celiac patients are not satisfactorily covered when formulation and production of gluten-free products is carried out [3].…”
Section: Introductionmentioning
confidence: 99%